2021
DOI: 10.1097/tgr.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Blood Tests of Lower Limb Joint Replacement for the Treatment of Osteoarthritis

Abstract: The purpose of this brief report was to identify the differences in blood investigations between total hip and knee replacement. We evaluated 80 consecutive patients who underwent hip (40) or knee (40) replacement, by examining pre-and postoperative blood samples. Preoperative blood tests were performed within 30 days prior to surgery, while postoperative blood tests were performed within 24 hours after surgery. We did not find any statistically significant difference between pre-and postoperative hematologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Thus, in the last decades, scientists have focused their attention on the identification of pain biomarkers in order to obviate a possible misdiagnosis, delayed clinical results and useless therapies [ 7 , 26 ]. Considering pain as the main symptom of their pathologies, FM and OA subjects, as other chronic pain patients, need urgent answers about the classification of their pain in order to undertake the best-tailored therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the last decades, scientists have focused their attention on the identification of pain biomarkers in order to obviate a possible misdiagnosis, delayed clinical results and useless therapies [ 7 , 26 ]. Considering pain as the main symptom of their pathologies, FM and OA subjects, as other chronic pain patients, need urgent answers about the classification of their pain in order to undertake the best-tailored therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the end, the utilization of a specific diagnostic biomarker could lead to an accurate recognition of the pain intensity, facilitating the prescription of the most suitable drug for the best patient management [ 27 , 31 ]. FM patients, for example, are usually overloaded by medical visits and pharmacological treatments because of psychiatric and psychological problems and/or biological and social environmental characteristics associated with their pathology [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The debate on whether mechanical and neutral tibial alignment is associated with superior durability and survivorship following TKA continues to garner interest as alternative alignment techniques show functional advantages [ 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. One recent long-term follow-up study (>10 years) supported the safety of alignment outside of the mechanical range (0 ± 3°); however, the tibia component varus was not specifically assessed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a pro-inflammatory cytokine that induces the expression of a variety of proteins responsible for acute inflammation [ 28 , 49 ].…”
Section: Synovial Fluid Proteome In Osteoarthritismentioning
confidence: 99%
“…Yu et al [ 49 ], in a prospective study that recruited 139 patients affected by hip or knee PJI, showed synovial IL-6 has a higher diagnostic accuracy for PJI, compared with synovial fluid CRP. These authors recommend assessing synovial IL-6 in patients with an increased serum IL-6 [ 49 ].…”
Section: Synovial Fluid Proteome In Osteoarthritismentioning
confidence: 99%